Normalization of previously shortened telomere length under treatment with imatinib argues against a preexisting telomere length deficit in normal hematopoietic stem cells from patients with chronic myeloid leukemia - Brümmendorf, Tim Henrik; Ersöz, Inci; Hartmann, Ulrike; Balabanov, Stefan; Wolke, Holger; Paschka, Peter; Lahaye, Tanja; Berner, Birgit; Bartolovic, Kerol; Kreil, Sebastian; Berger, Ute; Gschaidmeier, Harald; et al. (Annals of the New York Academy of Sciences, 2003)
Abstract: Telomeres are composed of TTAGGG repeats and associated proteins. In somatic cells, telomere repeats are lost with each cell division, eventually leading to genetic instability and cellular senescence. In previous studies, we described substantial and disease stage-specific telomere shortening in peripheral blood (PB) leukocytes from patients with chronic myeloid leukemia (CML). Here, we sought to determine whether age-adjusted telomere length in PB granulocytes (delta℡gran) is associated with response to treatment with the selective tyrosine kinase inhibitor imatinib. A total of 517 samples from 206 patients in chronic phase (CP), accelerated phase (AP), and blast crisis (BC) before and up to 706 days after initiation of imatinib therapy (median: 144 days) were analyzed by quantitative fluorescence in situ hybridization of interphase cells in suspension (Flow-FISH); telomere fluorescence was expressed in molecular equivalents of soluble fluorochrome units (MESF). Telomere length in samples from start of treatment up to day 144 was significantly shorter (mean ± SE; −1.5 ± 0.3 kMESF) compared to samples from patients treated for more than 144 days (−0.8 ± 0.3 kMESF, p= 0.035). In patients with repeated measurements, a significant increase in telomere length under treatment was observed. Median telomere length in major remission was found to be significantly longer compared to patients without response to treatment measured either by cytogenetics (n= 246, p < 0.05), interphase FISH (n= 204, p= 0.002), or quantitative RT-PCR (n= 371, p < 0.05). In conclusion, the increase in telomere length under treatment with imatinib reflects a shift from Ph+ to Ph− cells in the PB of patients with CML.
Elektronische Reproduktion der Druckausgabe
Gesehen am 13.05.2022